Age trend and risk factors of height loss in Chinese over 40 years old - Li, Yong-Fang; Xu, Lu-Lu; Wang, Qin-Yi; Luo, Chuo; Yue, Chun; Liu, Hong; Sheng, Zhi-Feng (Frontiers in Endocrinology, 2025)
IntroductionTo evaluate age-related height loss trend in men and women in China, and analyze associated risk factors, we conducted a cross-sectional study among 1286 participants from the Bone Health Improvement Program.MethodsLaboratory data were derived from the medical system and clinical risk factors of osteoporosis and fracture were collected through questionnaires. BMD was measured by DXA. Height loss was calculated as the difference between currently measured height and the highest self-reported height.ResultsThe study cohort comprised 706 males and 580 females, aged between 40 and 80 years, categorized into four age groups. The average height loss among men aged 70–80 was 9.5 times greater than men aged 40-50, while for women it was found to be 7.2 higher. Both genders experienced accelerated height loss after age 60; furthermore, women lose their height faster than men across all age groups. Multivariate logistic regression analysis including clinical risk factors, the best predictors of male height loss ≥4 cm were age (OR = 1.182, 95% CI: 1.111-1.258), rheumatoid arthritis (OR = 0.857, 95% CI: 0.788-0.933) and type 2 diabetes (OR = 3.012, 95% CI: 1.193-7.604), while for women, it was age (OR = 1.278, 95% CI: 1.182-1.382) and height (OR = 0.802, 95% CI: 0.714-0.901). In the multivariate logistic regression analysis involving laboratory data, the best predictive factors for male height loss ≥4 cm were eosinophil ratio (OR = 1.448, 95% CI: 1.11-1.89), fasting plasma glucose (OR = 0.469, 95% CI: 0.287-0.768), glycated hemoglobin (OR = 5.65, 95% CI: 2.511-12.711), and serum sodium levels (OR = 1.328, 95% CI: 1.112-1.585), while females had platelets counts (OR = 0.994, 95%CI: 0.989-1.000), glycated hemoglobin (OR = 1.413, 95% CI: 1.090-1.832), blood urea nitrogen levels (OR = 1.416, 95% CI: 1.147-1.747) and serum globulin levels (OR = 1.092, 95% CI: 1.01-1.18). The ROC curve areas for the models were 92.6%, 87.3%, 79%, and 68.1%, respectively.DiscussionIn Chinese aged over 40 years, the rate of height loss significantly accelerates after age 60, regardless of gender. The discovery of risk factors associated with height loss is beneficial for the early identification of individuals with height loss ≥4 cm, to facilitate the early detection of bone loss and enable further examination and treatment.